KONSEP PERSONAL BRANDING DALAM PERSPEKTIF HADIS NABI: ANALISIS TERHADAP HADIS RIYA' DAN SUM'AH - Zikri Darussamin; Afdhal Nabil Makarim (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
The development of social media has encouraged the practice of personal branding as a means of building identity and self-reputation in the digital space. This phenomenon raises ethical issues related to the potential of riya' and sum'ah in the perspective of the hadith of the Prophet This research aims to analyze the concept of personal branding in the perspective of hadith and formulate ethical limits for its application in the digital era. The research uses a qualitative method with a thematic hadith approach (mauḍū'ī) through literature studies. Data was obtained from hadiths related to riyā' and sum'ah, then analyzed using hadith syarah books and relevant scientific literature. The results of the study show that the hadith of the Prophet does not reject all forms of self-representation in the public sphere, but emphasizes the importance of intention, honesty, and interest orientation. Personal branding is allowed if it aims to introduce competence and provide benefits, while the orientation to praise and popularity is solely included in the categories of riya' and sum'ah. Thus, the hadith of the Prophet provides an ethical basis in building a digital reputation that is in line with Islamic values so that the use of social media remains within the corridor of sharia.